Understanding Cultural Sensitivity in Autism Education: A Semi-structured Interview among Chinese American Parents of Children with Autism - Yang, Xihan. (Tufts University. Tisch Library., 2024)
Thesis (M.A.)--Tufts University, 2024.; Submitted to the Dept. of Child Development.; Advisor: Eileen Crehan.; Committee: Eileen Crehan, Ellen Pinderhughes, and Christina Sakai.; Keywords: Education, Cultural resources management, and Disability studies.